Efeito do tratamento superficial em ligações de aço e concreto com adesivo epóxi - Pedro Henrique Almeida (2016)
This work refers to a research study aimed at evaluating the effect of superficial treatment in steel-concrete connection using of structural epoxy adhesive under shear stresses. This adhesive may be employed in structural joints conformed as steel-epoxy-steel and concrete-epoxy-steel. In diverse industries it is a substitute, as well as, an auxiliary measure to some conventional methods for bonding structural elements, such as riveting, soldering and/or bolting. Epoxy structural adhesive may also be used in concrete structures. However, successful adhesion depends on the adequate preparation of substrates (also referred to as adherends), as it also depends on controlling the conditions for the curing process in the adhesive. In order to determine the impact of surface treatment, test bodies of joints in steel-epoxy-steel and concrete-epoxy-steel were assembled with surfaces whose preparation varied from no treatment at all, to minimal treatment (cleaning and abrasion). This was meant to somewhat represent real conditions for the gluing process in a non-controlled environment. Results are presented comparatively. Following up, an analytical model was used to evaluate the stresses in the adhesive layer. Furthermore, Fourier Transform Infrared Spectroscopy (FTIR) was leveraged to characterize the epoxy adhesive and its interaction with substrates. Also, a Dynamic Mechanical Analysis (DMA) was employed in order to calculate the vitreous temperature transition for the adhesive, therefore assessing its thermal stability. We conclude that several results and analyses point that superficial treatment is adequate to the adhesion structural function proposed.